The interconnection of Maṣlaḥah in Traditional Market Management Policy during the Pandemic in the City of Yogyakarta - Muzalifah Muzalifah; Kamsi Kamsi; Ali Sodiqin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: The COVID-19 pandemic has an impact on all aspects of community life. The central government stipulates rules for limiting community activities that have an impact on the community's economic decline. This condition becomes the basis for the Yogyakarta City Government in making anticipatory and adaptive policies in the management of traditional markets. The policy is oriented towards achieving two benefits at once, namely the protection of life and property. This article analyzes the policies of the Yogyakarta City Government in managing traditional markets during the pandemic and to what extent these policies can achieve social and economic protection for the community. The analysis of these problems uses the maqâşid al-sharîa approach with the interconnectivity theory of maşlaḥah. The results show that the Yogyakarta City government's policy places social protection (ḥifẓ an-nafs) and economic protection (ḥifẓ al-mâl) as the interests of the community that must be protected. The Yogyakarta City Government continues to implement the central government's instructions by limiting operating hours and the number of visitors to traditional markets, but at the same time reducing user fees and encouraging online shopping promotions. The protection of the two benefits is carried out interconnectively, so that the achievement of one benefit does not cause damage to the fulfillment of the other's needs. The Yogyakarta City Government places these two protections as primary needs that must be protected so as not to cause social and economic damage.Abstrak: Pandemi covid-19 berdampak pada semua aspek kehidupan masyarakat. Pemerintah pusat menetapkan aturan pembatasan kegiatan masyarakat yang berdampak pada menurunnya ekonomi masyarakat. Kondisi ini menjadi dasar bagi Pemerintah Kota Yogyakarta dalam membuat kebijakan yang antisipatif dan adaptif dalam pengelolaan pasar tradisional. Kebijakan tersebut berorientasi pada pencapaian dua kemaslahatan sekaligus, yaitu perlindungan jiwa dan harta. Artikel ini menganalisis bagaimana kebijakan Pemerintah Kota Yogyakarta dalam pengelolaan pasar tradisional pada masa pandemi dan sejauh mana kebijakan tersebut dapat mewujudkan perlindungan sosial dan ekonomi masyarakat. Analisis terhadap masalah tersebut menggunakan pendekatan maqâşid al-sharî’a dengan teori interkoneksitas maşlaḥah. Hasil penelitian menunjukkan bahwa kebijakan Pemerintah Kota Yogyakarta mendudukkan perlindungan sosial (ḥifẓ an-nafs) dan perlindungan ekonomi (ḥifẓ al-mâl) sebagai kepentingan masyarakat yang harus dilindungi. Pemerintah Kota Yogyakarta tetap menerapkan instruksi pemerintah pusat dengan membatasi jam operasional dan jumlah pengunjung pasar tradisional, namun pada saat yang sama memberikan pengurangan retribusi dan menggiatkan promosi belanja online. Perlindungan kedua kemaslahatan tersebut dilaksanakan secara interkonektif, sehingga pencapaian kemaslahatan yang satu tidak berdampak kerusakan pada pemenuhan kemaslahatan yang lain. Pemerintah Kota Yogyakarta menempatkan kedua perlindungan tersebut sebagai kebutuhan primer yang harus dilindungi sehingga tidak menimbulkan kerusakan sosial dan ekonomi.